Exploring The Self-Awareness Of Dental Students And House Surgeons Regarding Oral Cancer: A Qualitative Study On Control And Prevention Strategies - Orakzai, Gulmina Saeed; Farooq, Mariya; Ali, Misbah; Gillani , Syeda Munazza; Awal, Jayyad Salim; Ilyas, Raif (Journal of Rawalpindi Medical College, 2024)
Objective: This qualitative study is carried out to get insights regarding various factors contributing to the high prevalence of this cancer and preventive strategies by dental students and house officers. Method: This qualitative research was conducted from June 2023 to Dec 2023, at Watim dental college Rawalpindi. Factors perceived to be related to oral cancer were investigated using the focus group discussion (FGD) method. A total of 20 participants (10 final-year students and 10 house surgeons) voluntarily participating in the study were included. Data were transcribed verbatim and thematic analysis was done. Results: All participants concurred on the severity of oral cancer as a major public health issue in Pakistan and many of them considered tobacco as a major risk factor. Risk factors, control and preventive strategies were summed up under major themes identified as alarming health issues, lifestyle and culture-related risk factors, issues in the dental curriculum and challenges in clinical set-up hampering thorough examination of oral cancer and related risk factors education. Conclusion: This present study suggests that formal dental education and clinical training are insufficient to cater for this major oral health issue and its associated risk factors. Rigorous measures should be taken to strengthen our existing undergraduate dental curriculum and incorporate courses at the undergraduate level for better understanding and training in this particular field to help them grapple with this rapidly rising health concern.